Redescription of enigmatic spider genus Stoliczka O. Pickard-Cambridge, 1885 (Araneae: Lycosoidea) based on the type species - Marusik, Yuri M.; Nadolny, Anton A. (Zootaxa, 2018)
The type species of Stoliczka O. Pickard-Cambridge, 1885—S. insignis O. Pickard-Cambridge, 1885—is redescribed for the first time, based on a lectotype here designated. The genus has an uncertain taxonomic position. Originally, it was placed in Lycosidae, while it is currently considered a Pisauridae (Pisaurinae). It includes only two species known from the Western Himalayas, of which the type species remains known only from the females and S. affinis Caporiacco, 1935, which is known from a juvenile only. An uncommon behavioral feature of these spiders is the attachment of egg cocoons to the spinnerets like in the Lycosidae. The absence of the male does not allow us to clarify the taxonomic assignment of this enigmatic genus.